Environmental chemistry and toxicology of mercury - Liu, Guangliang, 1972-; Cai, Yong, 1961-; O'Driscoll, Nelson J., 1973- (Wiley, 2012)
"Reviewing the major environmental processes of mercury (Hg) transformation and transport during Hg cycling, this book focuses on the recent developments in environmental chemistry of Hg. Each chapter touches on the basic concepts and provides a critical review of the targeted subject, the methodology used for studying it, and future research needs. The book outlines the fundamental concepts and provides a detailed review of critical findings in recent research. It is suitable for anyone interested in environmental sciences"--